Viral hit. Volume 1 - Pak, Taejun; Junghyun, Kim (WEBTOON Unscrolled, Wattpad WEBTOON Studios, 2025)
For readers who love over-the-top action and adventure, this global phenomenon WEBTOON comic with over 2 billion reads worldwide, from the creator of Lookism, follows the story of Hobin Yu, who rises from the bottom of his school hierarchy by streaming his fights. Scrawny high school student Hobin Yu is probably the last guy you'd expect to star in a video channel that revolves around fighting. Tormented by bullies and working a part-time job to pay for his mother's medical expenses, Hobin Yu is truly at the bottom of his school's hierarchy. After he accidentally uploads a video of a fight with his classmate and goes viral, Hobin starts to think there may be another solution to his bullying and money problems. After following some advice from a mysterious creator, Hobin is soon knocking out guys stronger than him and raking in more money than he ever dreamed. But the pressure starts to build, and one day Hobin might meet his match.